SARS-CoV-2 infection/vaccination associated new or exacerbating immune-mediated disease - Finsterer, Josef; MD , Fulvio A Scorza; MD , Ana C Fiorini (Jour Med Resh and Health Sci, 2021)
With interest we read the article by Watad et al. about 27 patients developing flares of or new immune-mediated disease (IMD) in association with a SARS-CoV-2 infection or vaccination [1].